Efektivitas Layanan Konseling Kelompok dalam Mengurangi Kecanduan Game Online pada Siswa - Tasya Maulana; Dina Sukma (Lembaga Yasin AlSys, 2024)
The experience of playing online games can make players feel happy and can eventually lead to addiction or dependence. Online game addiction can have an unfavorable impact on several aspects of student life. The purpose of this study is to see the effectiveness of the implementation of group counseling services in reducing online game addiction. This study used a quantitative approach using experimental methods. The research design used is pre-experiment, using a one group pretest and posttest design. The population in this study were phase F students at SMA Negeri 1 Lubuk Basung, the sampling technique used purposive sampling technique, then based on the appropriate criteria, 12 students were obtained who experienced online game addiction. The technique used to collect data is by distributing online game addiction scales, then the results are analyzed using the Wilcoxon Signed Ranks Test formula. The results showed that the implementation of group counseling services was effective in reducing online game addiction in students at SMA Negeri 1 Lubuk Basung. In particular, the use of group counseling services can significantly reduce online game addiction.